Mechanism of diabetic nephropathy and traditional drugs for management - Shabnam Ansari (Wolters Kluwer Medknow Publications, 2020)
Diabetic nephropathy (DN) is a microvascular complication of diabetes mellitus which affects the kidneys. Recent reports of increasing prevalence of diabetes around the globe suggested that that the prevalence of DN will be doubled by 2025. There is an extremely high risk of progression of DN to end-stage renal disease and cardiovascular morbidity and mortality. Control of sugar levels, blood pressure control via renin-angiotensin-aldosterone system inhibition, and regular monitoring of renal functions have remained the principle of the management for DN for a long time. As conventional drugs cannot fulfill all the clinical needs due to accessibility, clinical efficacy, and safety issues, the need for novel inexpensive traditional drugs from Unani medicine to improve DN treatment and reduce the risk of complications has become urgent. Several herbal and mineral drugs have been mentioned in the old Unani books for the treatment of similar conditions stipulating DN. Through this article, an uttermost effort has been put to rememorize the mechanism of development of DN and available Unani drugs so that effect and mechanism of these drugs could be evidenced in the treatment of DN in future.